IMPORTANCE OF IMPROVING WRITING SKILLS IN ENGLISH LANGUAGE (Konferensiyalar | Conferences, 2024)
In this article discusses, the above principles should be observed in students' acquisition of knowledge of language material and the formation of skills specific to the types of speech activities, students studying foreign languages should know and be able to do the following, and we, foreign language teachers, should teach students studying a foreign language the importance of writing in developing foreign language skills. It is said that we need to teach writing skills to future foreign language teachers by studying the typological features of the exercises given in textbooks and manuals for the implementation of communicative relations with other foreign countries.